Polish-accented English in prominent Polish politicians: the case of Donald Tusk - Marcin Mizak (Facta Simonidis)
The aim of this paper is to provide an exemplification of selected, consonantal features of Polish-accented English on the basis of a biographical interview conducted with a prominent Polish politician, Donald Tusk. Typical examples of Polish-accented English, such as final obstruent devoicing, plosive insertion after /ŋ/, lack of linking /r/ or various sound substitutions, are presented in the paper. The paper finishes with concluding remarks which briefly recapitulate its main points and suggest further analyses within the field of Polish-accented English.